Land Use and Land Cover (LULC) Change in Eastern Areas of East Java From 1972 To 2021: Learning From Landsat Image - Marga Mandala; Indarto Indarto; Ach. Fauzan Mas'udi; Akhmad Andi Saputra (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Urban development, population growth, high traffic jams, and intensive disaster events are indicators of changing the landscape of the eastern area of East Java. Investigating these changes is vital for planning and environmental protection in the future. This study examines changes in land use and land cover (LULC) during the past 50 years in the eastern part of East Java from 1972 to 2021. The changes are examined by contrasting four maps derived from Landsat images (1972, 1997, 2013, and 2021). The following are the main study procedures: (1) data inventory, (2) field survey, (3) image processing and classification, and (4) interpretation of LULC changes. With Google Earth Engine, all photos are downloaded (GEE). Landsat image classification was completed using the maximum likelihood algorithm with an overall Kappa accuracy of>85%. Eight (8) major classifications are therefore produced by the classification: (1) the pavement or urban area (PUA); (2) heterogeneous agricultural land (HAL); (3) bare soil (BS); (4) paddy field (PF); (5) open water body (OWB); (6) vegetation/plantation (VG); (7) shrubland (SL); and (8) wetlands (WL). In the areas with rapid development, the LULC change is more pronounced, i.e., Pasuruan, Jember, and Banyuwangi Regencies. LULC change in and near mid-regency and the rural regions comes next. Over the past fifty years, regional growth has resulted in increases in PUA (+4.4 percent), PF (+12.2 percent), and VG (+17.9 percent). On the other hand, the development has decreased SL, BS, and HAL by 5.8 and 15.9 percent, respectively (-13.1 percent ). LULC alterations for human activities have profoundly altered the natural landscape. Keywords:  East Java, GEE, Image Processing, Landsat, LULC